Time-dependent effects of prognostic biomarkers of systemic inflammation in patients with metastatic renal cell carcinoma - Wayne B Harris; Chao Zhang; Yuan Liu; Dale K Robertson; Mikhail Y Akbashev; Brian M Lingerfelt; Omer Kucuk; Bradley C Carthon; Theresa W Gillespie; Adeboye O Osunkoya; Viraj A Master (Tumor Biology)
The goal of this study was to examine time-dependent effects of prognostic biomarkers of systemic inflammation in patients with metastatic renal cell carcinoma. Retrospective chart reviews were conducted at the Winship Cancer Institute of Emory University and the Atlanta Veterans Administration Medical Center with authorization from the Emory University Institutional Review Board and the Veterans Administration Research and Development Committee. Inclusion criteria included age ⩾18 years, treatment with targeted therapy for clear cell or non–clear cell metastatic renal cell carcinoma and concomitant assessment of C-reactive protein and albumin levels on ⩾3 occasions that were ⩾10 days apart. Discovery, expansion, and external validation cohorts were identified. Established prognostic variables were evaluated by univariate and multivariate analyses. Intensity of systemic inflammation was assessed at all time points with C-reactive protein and albumin as prognostic covariates for overall survival in an extended Cox regression model. Intensity of systemic inflammation was assessed on 3186 occasions in 181 patients. Risk status changed in 131 patients (72%). The hazard ratio for overall survival was 21.41 (95% confidence interval = 8.26–55.50) with a type 3 p value of <0.001 for the reference cohort and 9.68 (2.07–45.31) with a type-3 p value of 0.006 for the external validation cohort when time points associated with severe systemic inflammation were compared to all other time points. The bias-corrected c-statistic was 0.839 (0.773–0.905) and 0.818 (0.691–0.946), respectively. Terminal disease progression with severe systemic inflammation was detected in 87% of the 90 patients who died. In conclusion, time-dependent effects are a prominent feature of intensity of systemic inflammation, a powerful prognostic biomarker for metastatic renal cell carcinoma.